2012
DOI: 10.1111/j.1471-4159.2012.07707.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐Terminal pyroglutamate formation of Aβ38 and Aβ40 enforces oligomer formation and potency to disrupt hippocampal long‐term potentiation

Abstract: J. Neurochem. (2012) 121, 774–784. Abstract Pyroglutamate (pGlu)‐modified amyloid peptides have been identified in sporadic and familial forms of Alzheimer’s disease (AD) and the inherited disorders familial British and Danish Dementia (FBD and FDD). In this study, we characterized the aggregation of amyloid‐β protein Aβ37, Aβ38, Aβ40, Aβ42 and ADan species in vitro, which were modified by N‐terminal pGlu (pGlu‐Aβ3‐x, pGlu‐ADan) or possess the intact N‐terminus (Aβ1‐x, ADan). The pGlu‐modification confers rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 37 publications
3
88
0
2
Order By: Relevance
“…Two key observations support this theory: 1) familial AD mutations in APP elevate the expression of Aβ1-42 [24,25]; and 2) Aβ1-42 is more prone to aggregation and is more toxic than Aβ1-40 [26,27]. However, it was reported that pyroglutamate-Aβ, which is also presented in AD plaques, could also be the toxic isoform of Aβ [28][29][30][31]. Pyroglutamate-Aβ is more prone to aggregation compared with Aβ1-42 [29].…”
Section: Challenges In Targeting Amyloidmentioning
confidence: 90%
See 1 more Smart Citation
“…Two key observations support this theory: 1) familial AD mutations in APP elevate the expression of Aβ1-42 [24,25]; and 2) Aβ1-42 is more prone to aggregation and is more toxic than Aβ1-40 [26,27]. However, it was reported that pyroglutamate-Aβ, which is also presented in AD plaques, could also be the toxic isoform of Aβ [28][29][30][31]. Pyroglutamate-Aβ is more prone to aggregation compared with Aβ1-42 [29].…”
Section: Challenges In Targeting Amyloidmentioning
confidence: 90%
“…However, it was reported that pyroglutamate-Aβ, which is also presented in AD plaques, could also be the toxic isoform of Aβ [28][29][30][31]. Pyroglutamate-Aβ is more prone to aggregation compared with Aβ1-42 [29]. Mice overexpressing this peptide showed a selective hippocampal neurodegeneration [31], and passive immunization against this peptide reduces the amyloid burden in an APP/PS1 double-transgenic mouse model [30].…”
Section: Challenges In Targeting Amyloidmentioning
confidence: 99%
“…Thus, meprin β might be involved in the generation of potentially more toxic species of Aβ, especially in the formation of Aβ3-40/42, which, in turn, is converted by glutaminyl cyclase into the aggregation prone pGlu3-Aβ. This Aβ species is targeted currently in clinical trials [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[116,117] These peptides are considered to be more toxic than the full-length ones, [118][119][120][121][122][123][124][125][126][127][128][129][130][131] given their connection to modified plaque morphology, hampered degradation of the pyroglutamate forms, higher propensity to form -sheets, and impact on the process of aggregation of the full-length peptides. The formation of pyroglutamate at the 11-position (see above) is also possible, but its effect has been less studied.…”
Section: Other Motifsmentioning
confidence: 99%